FIRST FIND OF POTASSIC BASALT IN VOLCANIC ROCKS IN THE MAGADAN REGION OF THE OKHOTSK-CHUKOTKA VOLCANIC BELT - Zakharov M.N.; Bobrov Y.D.; Tauson L.V. (My University, 1989)
Ore fields in the Arman intrusive-extrusive ring structure in the Okhotsk sector of the Okhotsk-Chukotka volcanic belt (OCVB) contain distinctive subintrusive bodies of automagmatic quartz-latite breccias and potassic basalt dikes. No analogs of these bodies have hitherto been found in volcanic rocks. We studied the rock sequences in the Khatachan depression in the southern part of the Arman structure, where the youngest rock is the basalt of the Mygdykit Formation, whose sequence consists of generally similar subalkalic basalt lavas with a sodium bias. In the Magadan region of the OCVB, basaltic lavas exhibit a pronounced sodium bias and our shoshonite is an exotic rock, that formed as a result of locally distinctive crystallization behavior of the melt. It thus cannot be treated as an independent shoshonite association of an active continental margin. The high concentration of incoherent elements and the high values of the Tauson rare metal index in the shoshonite are evidence of the passage of a plutonic fluid, indicating the potential presence of ore in the shoshonite lava.